2018
DOI: 10.2139/ssrn.3116054
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of High School Financial Education on Financial Knowledge and Choices: Evidence from a Randomized Trial in Spain

Abstract: We conducted a randomized controlled trial where 3,000 9 th grade students coming from 78 high schools received a financial education course at different points of the year. Right after the treatment, test performance increased by 16% of one standard deviation, treated youths were more likely to become involved in financial matters at home and showed more patience in hypothetical saving choices. In an incentivized saving task conducted three months after, treated students made more patient choices than a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 52 publications
3
34
1
1
Order By: Relevance
“…Despite the increasing number of studies that focus on similar issues (e.g., the effect of financial education on financial behavior; for a meta-analysis of experimental studies see [10]), hitherto, a surprisingly small number of studies tackled the described problem either theoretically or empirically. To our knowledge, in the only empirical papers [11][12][13] directly combining income, financial literacy and economic decision-making, the authors found that financial literacy decreases time-discounting although the effects are rather small. Other than that, a recent review [5] presented a hypothesized complex model of a cognitive mechanism describing how can poverty affect economic preferences.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Despite the increasing number of studies that focus on similar issues (e.g., the effect of financial education on financial behavior; for a meta-analysis of experimental studies see [10]), hitherto, a surprisingly small number of studies tackled the described problem either theoretically or empirically. To our knowledge, in the only empirical papers [11][12][13] directly combining income, financial literacy and economic decision-making, the authors found that financial literacy decreases time-discounting although the effects are rather small. Other than that, a recent review [5] presented a hypothesized complex model of a cognitive mechanism describing how can poverty affect economic preferences.…”
Section: Introductionmentioning
confidence: 87%
“…Many programs that aimed to increase financial literacy, and consequently to improve financial behavior had been proposed in the last years. However, the recent evidence [10][11][12]57,60] showed that financial education has only a small effect on financial literacy and almost negligible effect on real-life financial behavior. At the same time, the duration of these effects is very limited, often lasting no longer than one year [57,61].…”
Section: Poverty Economic Preferences and Financial Literacy: What Dmentioning
confidence: 99%
“…Estes jovens na vida adulta carregarão essa educação financeira para garantir o bem-estar social (Gorla et al, 2016). Além dos tradicionais estudos mostrando associação de características socio-demográficas na educação financeira, alguns estudos já identificaram que o conhecimento financeiro tem forte dependência de habilidades matemáticas dos jovens (Bahrani, Holder & Patel, 2017, Amezcua & Everardo, 2017, Bover, Hospido & Villanueva, 2015Mancebón, Embún & Sancho, 2016;Hilgerth, Hogarth & Beverly, 2003).…”
Section: Implicações Práticasunclassified
“…The few notable exceptions areBecchetti and Pisani (2012),Bruhn, de Souza Leão, Legovini, Marchetti, and Zia (2016),Eissa, Habyarimana, and William (2014),and Bover, Hospido, and Villanueva (2018).…”
mentioning
confidence: 99%
“…Three notable exceptions areLührmann, Serra-Garcia, and Winter (2015), who measure the impact of a financial education program on time inconsistency among German students; Jamison, Karlan, and Zinman (2014), who look at the impact of school-based financial education on discounting, self-control, and risk tolerance;and Bover, Hospido, and Villanueva (2018), who analyzes the degree of students' patience through an incentivized task.…”
mentioning
confidence: 99%